Do European hospitals have quality and safety governance systems and structures in place?. (2nd February 2009) - Shaw, C; Kutryba, B; Crisp, H; Vallejo, P; Suñol, R
Abstract : Internal systems for quality and safety were assessed in 89 hospitals in six European states, by external teams using standardised criteria and procedures, as part of the Methods of Assessing Response to Quality Improvement Strategies (MARQuIS) project. The assessments were made primarily to identify the current use of quality management systems in the sample hospitals, and also to demonstrate a potential tool for comparable assessment of hospitals in general. The large majority of the hospitals had a formal, documented infrastructure to manage quality and safety, but a significant minority had no designated mission, programme or coordination. In two-thirds of hospitals, the governing body was active in defining policy and programmes for improvement, and received reports on quality, safety and patient satisfaction at least once a year. The brief on-site assessments identified systematic variations, within and between countries, in structures and processes of governance and to document the uptake of best practice. Unacceptable variations in practice could be reduced, to the benefit of consumers and providers, by developing and publishing basic organisational standards relevant to all European states. The simple assessment criteria designed for this project could be developed into a practical tool for self-assessment, peer review or benchmarking of hospitals across national borders. This assessment, combined with explicit, relevant and achievable standards, could provide a vehicle to promote the voluntary uptake of best practice and consistency in quality and safety among hospitals in Europe.